E-commerce and v-business : business models for global success - Barnes, Stuart, 1971-; Hunt, Brian (Butterworth-Heinemann, 2001)
E-Commerce and V-Business examines the impact of the Internet and associated technologies on two related aspects of business: electronic commerce and virtual organisation. Using a combination of recent theory and empirical evidence it demonstrates how forward thinking organisations are reaping considerable strategic advantage from exciting new business models in these areas. Such models require radical rethinking of many aspects of traditional business. The book covers many of the critical and contemporary issues stemming from these important new developments.